Design and development of artificial intelligence web-based content for online learning among undergraduates - Nur Hasheena, Anuar (Universiti Malaysia Sarawak (UNIMAS), 2017)
The Artificial in telligence (AI) course has been challenging for the undergraduate due to its appro'ach in understandi ng the problem solving techniques and the algebraic eq uations that has been appli ed in the rea l world. This study aims to evaluate the effectiveness of the content using web-based lea rning for Attificia llntelJigence course amon g unde rgrad uates. This study was conducted using quasi-experimental design with pre-test and post-test. Constructivist princ ipal and Jonassen's model has been adapted and appli ed in the deli very of AI co ntent using Schoology learning management system. Quantitative statistics was applied on the questi onnaire to ana lyse the data based on th e treatment group of students' satisfaction s. T here are 100 students participated in th e study. The va lid scores data collected from the both group are 22 and the va lid survey data coll ected is 24. The control group of students learned th e AI content through traditi ona l lecture while th e treatment gro up of students learned through an online platfonn ca ll ed Schoology. The data were analysed using descriptive anal ysis and inferenti al ana lysis. In concl usion , the study found that learning through constructed online platform as effective as learning in trad itional classroom. Collaborati on between course instructor and peers is the key to successful learning in both online and traditiona l cl assroom.